1997
DOI: 10.1111/j.1365-2621.1997.tb15013.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Stability of Goat Meat Patties as Affected by Breed Type and Feeding Regimen

Abstract: Ground meat patties were made using knife-separable lean (frozen-thawed) composites from meat-type (Spanish, Spanish ϫ Boer) goats assigned to two feeding regimens (feedlot or range) and fiber-type (Angora, Spanish ϫ Angora) goats assigned to the feedlot regimen. Weight losses from panfrying (mainly moisture loss) were 17.7 to 21.6%. Range meat-type goat samples had a higher proportion of total saturated fatty acids than the feedlot counterparts. After refrigerated storage, raw or cooked patties (aerobically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…The results also agreed with the findings of Das et al (2015) and Das et al (2012), who observed a retarded action of Bael pulp residue and Moringa oleiferia leaves extract on the oxidative rancidity of goat meat nuggets and goat meat patties, respectively. Similar results were also presented by Chowdhury et al (2005) and Rhee et al (1997), who also recorded similar results in minced goat meat and goat meat patties, respectively.…”
Section: Resultssupporting
confidence: 88%
“…The results also agreed with the findings of Das et al (2015) and Das et al (2012), who observed a retarded action of Bael pulp residue and Moringa oleiferia leaves extract on the oxidative rancidity of goat meat nuggets and goat meat patties, respectively. Similar results were also presented by Chowdhury et al (2005) and Rhee et al (1997), who also recorded similar results in minced goat meat and goat meat patties, respectively.…”
Section: Resultssupporting
confidence: 88%
“…This result is in agreement with other studies (Rhee et al, 1997;Bas et al, 2005;Ryan et al, 2007;Faucitano et al, 2008). The C18:ln-9 in tissues originates partly from this FA intake not being completely biohydrogenated in the rumen, and partly from de novo conversion of C18:0 by the A'^-desaturase enzyme in tissues.…”
Section: Effect Of Increased Concentrate Supplementation On Fa Compossupporting
confidence: 96%
“…Among convenient meat products, patties have got highest degree of preference among the urban meat eaters owing to ease of preparation and better taste. Breed (Rhee et al, 1997) variations, feeding regime (Swan et al, 1998) and age (Agnihotri, 2002) of the animals are reported to affect the quality and composition of goat meat patties. Studies have also been carried out on goat meat patties formulations, standardization of processing techniques (Sharma et al, 1992) and method of cooking (Pawar et al, 2000).…”
Section: Introductionmentioning
confidence: 99%